14 A life support-based comprehensive treatment regimen dramatically reduced in-hospital mortality of fulminant myocarditis patients. (24th April 2019) - Wang, Dao Wen; Jiang, Jiangang; Li, Sheng; Wang, Yan; Wang, Hong; Zuo, Houjuan; Zhou, Ning; ,
Abstract : Fulminant myocarditis is chiefly caused by viral infections. Its onset is rapid, progresses quickly, and may lead to severe heart failure, circulatory failure and cardiogenic shock in a short time. Its mortality can be up to 50%–70%. Most importantly, there are no treatment options, and no evidence-based international guidelines or expert consensus statements. Here we provide the first expert consensus – the Chinese Society of Cardiology Expert Consensus Statement on the Diagnosis and Treatment of Fulminant Myocarditis – based on data from our recent registered clinical trial. In this statement, we describe for the first time its clinical features and diagnostic criteria, and importantly, a new treatment regimen, 'life support-based comprehensive treatment regimen'. This comprehensive treatment regimen includes meticulous nutritional and fluid management, administration of glucocorticoid, immunoglobulin and antiviral agents, continuous renal replacement therapy, life-support treatments including application of mechanical respirator(s) and circulatory support systems, intraaortic balloon pulsation (IABP) and extracorporeal membrane oxygenation (ECMO) as well as cardiac pacing if needed. Our practice in multiple cardiac centres demonstrated effectiveness of this treatment by dramatically lowering the mortality of patients with fulminant myocarditis.